DUAL EDUCATION IN LEARNING ENGLISH - Yusupova Laylo Maksudovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Dual language education programs have become extremely popular. Although these programs share common characteristics, they vary in several respects. Programs use different languages and include students with varying characteristics. For instance, many of these programs include students with fluent English proficiency and those with limited English proficiency; students identified with learning disabilities and those who are gifted; and students who are economically advantaged and those who are disadvantaged. Two basic dual language program models are the 90–10 and 50–50 models. This article describes a unique 50–50 model that divides language of instruction by content area as well as by time.